A CysB regulator positively regulates cysteine synthesis, expression of type III secretion system genes, and pathogenicity in Ralstonia solanacearum. (4th February 2022) - Chen, Min; Zhang, Weiqi; Han, Liangliang; Ru, Xuejuan; Cao, Yuzhu; Hikichi, Yasufumi; Ohnishi, Kouhei; Pan, Guanghui; Zhang, Yong
Abstract: A syringe‐like type III secretion system (T3SS) plays essential roles in the pathogenicity of Ralstonia solanacearum, which is a causal agent of bacterial wilt disease on many plant species worldwide. Here, we characterized functional roles of a CysB regulator (RSc2427) in R . solanacearum OE1‐1 that was demonstrated to be responsible for cysteine synthesis, expression of the T3SS genes, and pathogenicity of R . solanacearum . The cysB mutants were cysteine auxotrophs that failed to grow in minimal medium but grew slightly in host plants. Supplementary cysteine substantially restored the impaired growth of cysB mutants both in minimal medium and inside host plants. Genes of cysU and cysI regulons have been annotated to function for R . solanacearum cysteine synthesis; CysB positively regulated expression of these genes. Moreover, CysB positively regulated expression of the T3SS genes both in vitro and in planta through the PrhG to HrpB pathway, whilst impaired expression of the T3SS genes in cysB mutants was independent of growth deficiency under nutrient‐limited conditions. CysB was also demonstrated to be required for exopolysaccharide production and swimming motility, which contribute jointly to the host colonization and infection process of R . solanacearum . Thus, CysB was identified here as a novel regulator on the T3SS expression in R. solanacearum . These results provide novel insights into understanding of various biological functions of CysB regulators and complex regulatory networks on the T3SS in R. solanacearum . Abstract : Ralstonia solanacearum CysB controls cysteine synthesis and positively regulates the type III secretion system (T3SS) expression through the PrhG to HrpB pathway. The cysB mutant is cysteine auxotroph, while its impact on the T3SS is independent of growth deficiency.